Factors affecting on bank’s profitability: the case of 19 Euro-Area countries - Nexhat Kryeziu; Egzon Hoxha (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
The paper has addressed as the main objective the assessment of productivity performance in euro-area nations, observing a combination of factors both in terms of the internal environment and external factors, or known as macroeconomic factors. The analysis includes 19 euro-area countries with 323 observations, including the period 2003-2019. The dynamic approach, the fixed-effect model, and the Arellano / Bond estimator were applied using the panel data to evaluate the study's factors. The analysis shows that the factors under the competence of their internal supervision impact the degree of profitability on the one hand. Macroeconomic factors also show an impact on the degree of profitability for euro-area countries. Five of the seven factors applied in the analysis turned out to significantly impact, while two turned out to be non-significant. For further studies, it would be beneficial to apply other dynamic models by using other specific factors, which will be considered a useful input to the financial industry and financial policy-making.